The ultimate book of sharks : your guide to these fierce and fantastic fish - Skerry, Brian; Carney, Elizabeth, 1981-; Flynn, Sarah Wassner (National Geographic kids., 2018)
A National Geographic explorer and photographer takes readers along on a dive beneath the ocean waves to explore many different kinds of sharks, discovering the smallest to the largest and what their life cycles, habitats, and diets are like.